Mo2C-loaded N and P co-doped carbon nanospheres as well as preparation method and application of Mo2C-loaded N and P co-doped carbon nanospheres
The Mo-EDTA complex formed by EDTA enables uniform dispersion of Mo2C on carbon nanospheres and N and P co-doping, solving the problems of Mo2C nanoparticle aggregation and weak interfacial coupling. This improves the stability and activity of the water electrolysis hydrogen production catalyst and provides a low-cost and efficient water electrolysis hydrogen production solution.
Patent Information
- Application Number
- CN202511546900.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2026-01-16
AI Technical Summary
Existing Mo2C nanoparticles tend to aggregate and grow during high-temperature carbonization, resulting in a decrease in active specific surface area and weak interaction with carbon supports, which limits the improvement of catalytic performance. Existing heteroatom doping strategies are complex and uneven, and cannot achieve efficient electronic structure regulation and structural stability improvement.
Ethylenediaminetetraacetic acid (EDTA) is used as a nitrogen source and chelating agent to form Mo-EDTA complex through self-polymerization reaction, thereby achieving uniform dispersion of Mo2C and co-doping of N and P, constructing a tight interface to enhance electronic coupling, avoid agglomeration and improve charge transport efficiency.
The prepared Mo2C-loaded N and P co-doped carbon nanospheres achieved monodisperse loading of Mo2C during high-temperature carbonization, reduced charge transfer impedance, significantly improved the long-term cycling stability and catalytic activity of the catalyst, reduced overpotential, and exhibited excellent performance in hydrogen production through water electrolysis.
Smart Images

Figure CN121344651A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical materials technology, and in particular to a Mo2C-loaded N, P co-doped carbon nanosphere, its preparation method, and its application. Background Technology
[0002] Hydrogen energy, with its advantages of zero carbon emissions, high energy density, and flexible storage, is widely recognized as the most promising next-generation energy carrier. The large-scale application of water electrolysis for hydrogen production is irreplaceable for achieving a clean energy transition. However, the energy consumption and cost of water electrolysis for hydrogen production have long constrained its industrialization, with the core bottleneck being the efficient and stable catalyst. Traditional water electrolysis catalysts are mainly Pt-based noble metal materials, which, while exhibiting excellent catalytic activity, face the practical dilemma of scarce reserves and high costs. While 3d transition metal-based and other non-noble metal catalysts are lower in cost, they suffer from insufficient stability and continuous performance degradation under industrial-grade high current density conditions, making it difficult to meet practical application requirements.
[0003] Transition metal carbides (especially Mo₂C) are considered one of the most promising alternatives to Pt due to their Pt-like d-electron structure, high conductivity, and excellent chemical stability. However, Mo₂C nanoparticles are prone to agglomeration and growth during high-temperature carbonization, leading to a decrease in the active surface area. Simultaneously, the problems of dissolution and oxidation in acid-base electrolytes remain unresolved, resulting in significant activity degradation over long-term operation. To address these issues, researchers have attempted to composite Mo₂C with carbon-based supports, such as carbon nanotubes, graphene, and mesoporous carbon, aiming to improve the utilization of active sites and inhibit particle agglomeration through the highly conductive network and porous structure of the support. Despite some progress, existing preparation methods struggle to achieve uniform dispersion of Mo₂C on the carbon support surface, and the weak interaction between the two limits the improvement in catalytic performance.
[0004] Therefore, developing a Mo2C-supported carbon carrier material with simple preparation process, excellent catalytic activity and reliable stability has become an urgent need to break through the bottleneck of water electrolysis hydrogen production technology and promote the industrialization of green hydrogen. Summary of the Invention
[0005] To address the challenges of achieving uniform dispersion of Mo2C on the surface of a carbon support and the weak interaction between the two, which limits the improvement of catalytic performance, this invention provides Mo2C-loaded N and P co-doped carbon nanospheres, their preparation method, and applications.
[0006] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: A method for preparing Mo2C-loaded N, P co-doped carbon nanospheres includes the following steps: S1, Phenolic substances and ethylenediaminetetraacetic acid are added to a mixed solution of anhydrous ethanol and water, the pH of the system is adjusted to weak alkalinity, aldehyde substances are added, and a self-polymerization reaction is carried out to obtain a phenolic resin oligomer reaction solution. S2, the phenolic resin oligomer reaction solution is heated to 70℃~90℃ for hydrothermal reaction, solid-liquid separation is performed, and the solution is dried to obtain phenolic resin nanospheres. S3, the phenolic resin nanospheres and phosphomolybdic acid are dispersed in water, stirred for 8-12 hours, separated into solid and liquid, dried, and calcined under an inert atmosphere to obtain Mo2C-loaded N and P co-doped carbon nanospheres.
[0007] Currently, Mo2C-based catalysts still face three major bottlenecks in practical applications: First, traditional high-temperature carbonization processes lack effective constraints, and Mo2C particles are prone to agglomeration and growth, leading to a sharp decrease in the active specific surface area and a large number of active sites being obscured; second, the interfacial coupling between the carbon support and Mo2C is weak, and the electron transfer impedance is high, which severely limits the charge transport efficiency and catalytic kinetics; third, existing heteroatom (N, P, etc.) doping strategies require additional precursors or multiple post-processing steps, which are complex and have poor doping uniformity, making it impossible to simultaneously achieve efficient electronic structure regulation and structural stability improvement.
[0008] Compared to existing technologies, the method for preparing Mo2C-loaded N and P co-doped carbon nanospheres provided by this invention introduces ethylenediaminetetraacetic acid (EDTA) during the synthesis of phenolic resin nanospheres. On the one hand, EDTA can serve as a nitrogen source, and the amino groups in its molecules can be simultaneously embedded into the resin framework during the polymerization of phenolic resin, providing a stable source for the subsequent N doping of carbon nanospheres. On the other hand, the chelating properties of EDTA can regulate the self-polymerization rate of phenols and aldehydes, avoiding the agglomeration of phenolic resin nanospheres caused by excessively rapid reactions. Thirdly, EDTA can form a strong coordination interaction with molybdenum ions in the system, firmly anchoring molybdenum ions to the surface of phenolic resin nanospheres, forming a uniform Mo-EDTA complex, achieving directional pre-loading of active metal components. Thus, during the subsequent high-temperature carbonization process, EDTA acts as a molecular cage to inhibit the agglomeration of Mo2C nanoparticles, achieving monodisperse anchoring, and also decomposes in situ to provide an N source, while synergistically releasing a P source from phosphomolybdic acid, achieving efficient and uniform doping of the carbon framework with N and P dual heteroatoms in one step. The resulting tight interface enables strong electronic coupling between the carbon support and the Mo2C active sites, significantly reducing charge transfer impedance. This, in turn, greatly reduces the HER overpotential while endowing the catalyst with excellent long-term cycling stability.
[0009] Furthermore, in S1, the phenolic substance is 3-aminophenol.
[0010] Furthermore, in S1, the aldehyde is formaldehyde.
[0011] Furthermore, in S1, the weak alkalinity refers to pH=9~10.
[0012] Furthermore, in S1, the temperature of the self-polymerization reaction is 20℃~40℃, and the reaction time is 3h~5h.
[0013] The optimized reaction conditions facilitate the gradual formation of phenolic resin oligomers with uniform molecular weight distribution, providing a precursor for the preparation of phenolic resin nanospheres with narrow particle size distribution and high sphericity. This, in turn, is beneficial for the uniform anchoring of the subsequent Mo-EDTA complex and the monodisperse loading of Mo2C.
[0014] Furthermore, in S1, the mass ratio of ethylenediaminetetraacetic acid to phenolic substances is (14~16):6.
[0015] The preferred mass ratio of EDTA to phenolic substances can, on the one hand, avoid insufficient formation of Mo-EDTA complex due to insufficient EDTA, which would result in low Mo2C loading and catalytic activity decay; on the other hand, excessive EDTA would lead to excessive thickening of the surface carbon layer, which would obscure active sites and inhibit the formation of Mo2C.
[0016] Further, in S1, the mass-volume ratio of the phenolic substance, anhydrous ethanol and water is 6:(1~2):(3~5).
[0017] Furthermore, in S1, the molar ratio of the phenolic substance to the aldehyde substance is (1~1.2):1.
[0018] Furthermore, in S2, the hydrothermal reaction time is 18h~24h.
[0019] A hydrothermal reaction time of 18-24 hours allows the phenolic resin oligomers generated in S1 to fully cross-link under high temperature and pressure conditions of 70-90℃. The active groups such as hydroxyl and methylene groups in the oligomers can completely react to form a dense three-dimensional network, avoiding the loose internal structure and poor mechanical strength of the nanospheres due to incomplete reaction. Simultaneously, sufficient cross-linking results in a smooth and regular morphology on the surface of the nanospheres, preventing unreacted oligomers from forming protrusions or impurities on the surface. This provides a smooth carrier interface for the uniform adsorption of phosphomolybdic acid in S3 and the stable anchoring of the Mo-EDTA complex. If the reaction time is less than 8 hours, the oligomer cross-linking is incomplete, and the nanospheres are prone to hollowness or porous structures. If the reaction time exceeds 24 hours, excessive cross-linking will cause the nanospheres to harden and become brittle, easily cracking during subsequent calcination and destroying the Mo2C supported structure.
[0020] Furthermore, in S3, the mass ratio of the phenolic resin nanospheres to phosphomolybdic acid is 1:(6~8).
[0021] At this mass ratio, phosphomolybdic acid can form a uniform adsorption layer on the surface of phenolic resin nanospheres. The loading ratio of phenolic resin nanospheres to phosphomolybdic acid is well-matched, avoiding both insufficient phosphomolybdic acid leading to localized concentration of Mo elements (which easily agglomerates into large Mo2C particles after calcination) and excessive phosphomolybdic acid causing the support to be unable to fully support the material. A ratio of 1:(6~8) allows phosphomolybdic acid to be tightly and uniformly anchored on the support surface. During subsequent calcination, the growth of Mo species is restricted by the carbon support, forming small-sized, highly dispersed Mo2C particles, avoiding the decrease in active specific surface area caused by agglomeration, and further improving catalytic activity and stability.
[0022] Furthermore, in S3, the mass-to-volume ratio of the phenolic resin nanospheres to water is 50 mg: (15~25) mL.
[0023] Furthermore, in S3, the calcination temperature is 750℃~850℃, the heating rate is 1℃ / min~5℃ / min, and the calcination time is 1.5h~2.5h.
[0024] The optimized calcination temperature, heating rate, and calcination time ensure that phosphomolybdic acid is efficiently converted into highly active Mo2C nanoparticles, while also allowing N and P atoms to be stably anchored in the carbon framework. At the same time, the porous structure of the carbon nanospheres is maintained, preserving channels for electrolyte mass transfer and electron transport.
[0025] The present invention also provides a Mo2C-loaded N, P co-doped carbon nanosphere, which is prepared by any of the above-described methods for preparing Mo2C-loaded N, P co-doped carbon nanospheres.
[0026] The present invention also provides an electrode comprising the above-mentioned Mo2C-loaded N and P co-doped carbon nanospheres.
[0027] The present invention also provides the application of the above-mentioned Mo2C-loaded N, P co-doped carbon nanospheres or the electrode described herein in hydrogen production by water electrolysis.
[0028] This invention uses 3-aminophenol-formaldehyde phenolic resin nanospheres as a carbon precursor and utilizes the multidentate coordination of EDTA with Mo ions to form a uniform Mo-EDTA complex. During one-step carbonization in an inert atmosphere, EDTA acts as a molecular cage to inhibit the aggregation of Mo2C nanoparticles, achieving monodisperse anchoring, and also releases N and P sources in situ to complete uniform doping with two heteroatoms. The prepared Mo2C-loaded N and P co-doped carbon nanospheres have a regular structural feature: they are solid carbon spheres of 700-900 nm, with 3-10 nm Mo2C nanoparticles uniformly distributed on their surface. In the electrolysis of water for hydrogen production performance test, this material exhibits excellent catalytic performance: in 1M KOH electrolyte, when the current density is 10 mA / cm²... 2At that time, the overpotential is ≤80mV, and the Tafel slope is 95~105mV / dec; it also has good long-term stability at 50mA / cm 2 Hydrogen evolution was continuously performed at a current density for 23 hours, with a current retention rate of ≥90%.
[0029] Furthermore, the preparation method of the present invention has the advantages of simple process, cheap and readily available raw materials, and easy industrial scale-up, which can provide a brand-new technical path and solution for the structural design and commercial application of low-cost, high-efficiency, and long-life water electrolysis hydrogen production catalysts. Attached Figure Description
[0030] Figure 1 The images shown are SEM and TEM images of Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention at different magnifications, where (a)-(c) are SEM images and (d)-(f) are TEM images. Figure 2 The image shows the XRD pattern of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1. Figure 3 XPS spectra of Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention, wherein (a) XPS full spectrum, (b) C 1s spectrum, (c) N 1s spectrum, (d) percentage of each element in the Mo2C-loaded N and P co-doped carbon nanosphere sample, (e) Mo 3d spectrum, and (f) P 2p spectrum; Figure 4 The Raman spectrum of Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention; Figure 5 The linear voltammetric scan (LSV) curve of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention in a KOH solution with a concentration of 1.0 mol / L is shown. Figure 6 Tafel slope diagram of Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention; Figure 7 The image shows a comparison of the LSV curves of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of the present invention before and after 1000 CV cycles in the non-Radida region in 1M KOH solution. Figure 8 The Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention were subjected to a current density of 50 mA / cm². 2 The current test diagram was obtained after 23 hours of constant potential under the condition of [condition missing]. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0032] To better illustrate the present invention, further examples are provided below.
[0033] Example 1 This embodiment provides a method for preparing Mo2C-loaded N and P co-doped carbon nanospheres, comprising the following steps: S1, under magnetic stirring, 60 mg of 3-aminophenol was dissolved in a mixed solution containing 40 mL of deionized water and 16 mL of anhydrous ethanol. After stirring evenly, 150 mg of ethylenediaminetetraacetic acid (EDTA) was added, and the pH of the system was adjusted to 9.26 with ammonia solution. After stirring for 30 min, 0.036 mL of 37 wt% formaldehyde was added, and the mixture was stirred at room temperature for 4 h to obtain phenolic resin oligomer reaction solution. S2, the phenolic resin oligomer reaction solution was transferred to a 125 mL Teflon container and hydrothermally reacted at 80°C for 20 h. Then, it was centrifuged at 11000 rpm for 5 min, the obtained phenolic resin nanospheres were collected, washed three times with water, and dried at room temperature to obtain phenolic resin nanospheres. S3, then 50 mg of dried phenolic resin nanospheres and 300 mg of phosphomolybdic acid (H3PMo) were added. 12 O 40 Add 20 mL of deionized water, stir at room temperature for 10 h, centrifuge at 11000 rpm for 5 min, collect the product, wash three times with water and dry at room temperature, then calcine at 800°C for 2 h under nitrogen atmosphere with a heating rate of 1 °C / min to obtain Mo2C-loaded N,P co-doped carbon nanospheres, denoted as N,P-Mo2C / NC-150.
[0034] Example 2 This embodiment provides a method for preparing Mo2C-loaded N and P co-doped carbon nanospheres, comprising the following steps: S1. Under magnetic stirring, 60 mg of 3-aminophenol was dissolved in a mixed solution containing 30 mL of deionized water and 10 mL of anhydrous ethanol. After stirring evenly, 140 mg of ethylenediaminetetraacetic acid (EDTA) was added, and the pH of the system was adjusted to 9.52 with ammonia solution. After stirring for 30 min, 0.036 mL of 37 wt% formaldehyde was added, and the mixture was stirred at room temperature for 3 h to obtain phenolic resin oligomer reaction solution. S2, the phenolic resin oligomer reaction solution was transferred to a 125 mL Teflon container and hydrothermally reacted at 70°C for 24 h. Then, the phenolic resin nanospheres were collected by centrifugation at 11000 rpm for 5 min, washed three times with water, and dried at room temperature to obtain phenolic resin nanospheres. S3, then 50 mg of dried phenolic resin nanospheres and 350 mg of phosphomolybdic acid (H3PMo) 12 O 40 Add 15 mL of deionized water, stir at room temperature for 8 h, centrifuge at 11000 rpm for 5 min, collect the product, wash three times with water and dry at room temperature, then calcine at 750°C for 2.5 h under nitrogen atmosphere with a heating rate of 5 °C / min to obtain Mo2C-loaded N,P co-doped carbon nanospheres, denoted as N,P-Mo2C / NC-200.
[0035] Example 3 This embodiment provides a method for preparing Mo2C-loaded N and P co-doped carbon nanospheres, comprising the following steps: S1, under magnetic stirring, 60 mg of 3-aminophenol was dissolved in a mixed solution containing 50 mL of deionized water and 20 mL of anhydrous ethanol. After stirring evenly, 160 mg of ethylenediaminetetraacetic acid (EDTA) was added, and the pH of the system was adjusted to 9.89 with ammonia solution. After stirring for 30 min, 0.036 mL of 37 wt% formaldehyde was added, and the mixture was stirred at room temperature for 5 h to obtain phenolic resin oligomer reaction solution; S2, the phenolic resin oligomer reaction solution was transferred to a 125 mL Teflon container and hydrothermally reacted at 90°C for 18 h. Then, it was centrifuged at 11000 rpm for 5 min, the obtained phenolic resin nanospheres were collected, washed three times with water, and dried at room temperature to obtain phenolic resin nanospheres. S3, then 50 mg of dried phenolic resin nanospheres and 400 mg of phosphomolybdic acid (H3PMo) were added. 12 O 40 Add 25 mL of deionized water, stir at room temperature for 12 h, centrifuge at 11000 rpm for 5 min, collect the product, wash three times with water and dry at room temperature, then calcine at 850°C for 1.5 h under nitrogen atmosphere with a heating rate of 3 °C / min to obtain Mo2C-loaded N,P co-doped carbon nanospheres, denoted as N,P-Mo2C / NC-100.
[0036] Material characterization Figure 1The images show SEM and TEM images of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 at different magnifications. SEM results show that the sample is a regular solid sphere with an average particle size of approximately 787 nm. TEM further confirms that the sample has no obvious porous structure and that metal particles are uniformly distributed on the surface of the carbon spheres. High-resolution TEM measurements show that the lattice spacing of these particles is 3.71 Å, corresponding to the (110) crystal plane of Mo2C, indicating that molybdenum has been successfully loaded onto the carbon support surface.
[0037] Figure 2 The image shows the XRD pattern of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1. The Mo2C-loaded N and P co-doped carbon nanospheres show a series of sharp diffraction peaks at 2θ = 34.4°, 37.9°, 39.5°, 52.1° and 61.5°, which are in perfect agreement with the (100), (002), (101), (102) and (110) crystal planes of hexagonal β-Mo2C (PDF#77-0720), confirming that the EDTA-Mo complex was successfully converted into well-crystallized Mo2C after pyrolysis.
[0038] Figure 3 The XPS spectrum of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention shows that the sample contains C (36%), N (13%), P (1%), O (24%), and Mo (26%), confirming the successful doping of metallic molybdenum and heteroatoms N and P. For the high-resolution C 1s XPS spectrum, two fitting peaks are observed at 284.8 eV and 286.5 eV, attributed to CC and CN bonds, respectively. Three different types of N were found in the N 1s spectrum, with peaks at 397.2 eV, 398.4 eV, and 401.1 eV belonging to pyrrole-N, pyridine-N, and graphitic-N, respectively. The presence of pyridine-N and pyrrole-N can enhance conductivity and electrochemical activity. Furthermore, the high-resolution XPS spectrum of Mo 3d can be fitted into two pairs of peaks, belonging to two different states (+δ, +6) in the Mo heterostructure. The binding energy peaks at 228.17 eV and 231.46 eV correspond to Moδ+ (0≤δ≤4) of the Mo-N coordination bond and the Mo-C bond of Mo2C, while the binding energy peaks at 232.47 eV and 235.6 eV correspond to Mo of MoO2. 6+ 3D 5 / 2 Mo, due to exposure to air, undergoes surface oxidation to form MoO3. 6+ 3D 3 / 2 .
[0039] The Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention were characterized by BET analysis. The results showed that the sample exhibited a typical type II isotherm, consistent with the non-porous physisorption characteristics of non-porous carbon materials, and had a specific surface area of 60.62 m². 2 / g.
[0040] Figure 4 The image shows the Raman spectrum of Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 of this invention. As can be seen from the image, the sample exhibits high Raman spectral density at 135 cm⁻¹. -1 (D band, disordered / defective carbon) and 1596 cm⁻¹ -1 (G-band, sp) 2 The graphite carbon (a type of graphite) exhibits a typical double peak. D / I G The ratio refers to the ratio of the D and G peak intensities, and is commonly used to indicate the degree of graphitization. The Ig of Mo2C-loaded N, P co-doped carbon nanospheres... D / I G A value of 0.98 indicates that it has abundant defect sites, which is beneficial for charge transfer and exposure of active sites. Furthermore, at 816 cm⁻¹... -1 With 989cm -1 Characteristic peaks attributable to Mo=O stretching vibration and Mo–O–Mo antisymmetric stretching vibration were observed. Their intensity decreased significantly with increasing carbonization temperature, confirming that high temperature promotes the deep reduction of molybdenum oxide to Mo2C, which is consistent with the XRD results.
[0041] Application examples 5 mg of Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 were placed in a 1.5 mL centrifuge tube, 950 μL of deionized water-anhydrous ethanol mixed solvent (volume ratio 1:1) was added, followed by 50 μL of 5 wt% Nafion solution. The mixture was ultrasonically dispersed for 30 min. 5 μL of the above slurry was pipetted and uniformly drop-coated onto the surface of a glassy carbon electrode. The coated glassy carbon electrode was then placed in a vacuum drying oven at 60 °C and dried for 2 h.
[0042] The prepared catalyst electrode was used as the working electrode. The Hg / HgO electrode (reference) and graphite rod (counter electrode) were respectively immersed in 1M KOH electrolyte, and linear sweep voltammetry (LSV) was performed at a rate of 5 mV / s. The results are as follows: Figure 5 As shown. At a current density of 10 mA / cm². 2 At that time, the hydrogen evolution overpotential of the Mo2C-loaded N and P co-doped carbon nanospheres prepared in Example 1 was 76.8 mV.
[0043] right Figure 5By fitting the linear region of the LSV curve, the Tafel curve is obtained, and its slope is the Tafel slope, which reflects the kinetic rate of the hydrogen evolution reaction. The fitted Tafel curve is shown in the figure. Figure 6 As shown, the Tafel slope is 100 mV / dec, indicating that it has relatively fast reaction kinetics, which is consistent with the LSV results above.
[0044] The Mo₂C-loaded N, P co-doped carbon nanospheres prepared in Example 1 were subjected to LSV curve testing in the non-Radidatic region of 1M KOH solution before and after 1000 CV cycles. The scan rate was 5 mV / s, and the LSV curves before and after the -0.2 ~ 0.3 V cycle test are shown in the figure below. Figure 7 As shown in the figure, the shift in the LSV curve of the Mo2C-loaded N and P co-doped carbon nanospheres after CV cycling is negligible.
[0045] The Mo2C-loaded N, P co-doped carbon nanospheres prepared in Example 1 were subjected to a current density of 50 mA / cm². 2 Under these conditions, a 23-hour constant potential current test (it) was conducted. After the test, the ratio of the current value after 23 hours to the initial current value was calculated, which is the current retention rate. The results are as follows: Figure 8 As shown. Experimental results show that at a current density of 50 mA / cm², 2 After continuous testing for 23 hours under the specified conditions, it still maintained a current retention rate of 91% and did not show significant current decay.
[0046] In summary, the Mo2C-supported N and P co-doped carbon nanospheres prepared in this embodiment of the invention are a highly efficient HER catalyst, exhibiting excellent catalytic performance and long-term stability under alkaline conditions. They provide a high-performance catalyst for low-cost, high-stability water electrolysis to produce hydrogen, and play a positive supporting role in promoting the green industrialization process and assisting in the clean energy transition.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing Mo2C-loaded N, P co-doped carbon nanospheres, characterized in that, The method comprises the following steps: S1, adding a phenolic substance and ethylenediaminetetraacetic acid into a mixed solution of anhydrous ethanol and water, adjusting the pH of the system to weak alkaline, adding an aldehyde substance, and performing a self-polymerization reaction to obtain a phenolic aldehyde resin oligomer reaction solution; S2, heating the phenolic aldehyde resin oligomer reaction solution to 70-90 DEG C to perform a hydrothermal reaction, performing solid-liquid separation, and drying to obtain phenolic aldehyde resin nanospheres; S3, dispersing the phenolic aldehyde resin nanospheres and phosphomolybdic acid in water, stirring for 8-12 hours, performing solid-liquid separation, drying, and performing calcination under an inert atmosphere to obtain Mo2C loaded N, P co-doped carbon nanospheres.
2. The method for preparing Mo2C-loaded N, P co-doped carbon nanospheres as described in claim 1, characterized in that, In S1, the phenolic substance is 3-aminophenol; and / or In S1, the aldehyde substance is formaldehyde.
3. The method for preparing Mo2C-loaded N, P co-doped carbon nanospheres as described in claim 1, characterized in that, In S1, the weak alkaline refers to pH=9-10; and / or In S1, the self-polymerization reaction is performed at a temperature of 20-40 DEG C for 3-5 hours.
4. The method for preparing Mo2C-loaded N, P co-doped carbon nanospheres as described in claim 1, characterized in that, In S1, the mass ratio of ethylenediaminetetraacetic acid to the phenolic substance is (14-16):6; and / or In S1, the mass-volume ratio of the phenolic substance, anhydrous ethanol and water is 6:(1-2):(3-5); and / or In S1, the molar ratio of the phenolic substance to the aldehyde substance is (1-1.2):
1.
5. The method for preparing Mo2C-loaded N, P co-doped carbon nanospheres as described in claim 1, characterized in that, In S2, the hydrothermal reaction is performed for 18-24 hours.
6. The method for preparing Mo2C-loaded N, P co-doped carbon nanospheres as described in claim 1, characterized in that, In S3, the mass ratio of the phenolic aldehyde resin nanospheres to phosphomolybdic acid is 1:(6-8); and / or In S3, the mass-volume ratio of the phenolic aldehyde resin nanospheres to water is 50 mg:(15-25) mL.
7. The method for preparing Mo2C-loaded N, P co-doped carbon nanospheres as described in claim 1, characterized in that, The calcination is performed at a temperature of 750-850 DEG C at a heating rate of 1-5 DEG C / min for 1.5-2.5 hours.
8. Mo2C supported N, P co-doped carbon nanospheres, characterized in that, The Mo2C loaded N, P co-doped carbon nanospheres are prepared by the method of any one of claims 1-7.
9. An electrode characterized by, The Mo2C loaded N, P co-doped carbon nanospheres of claim 8.
10. The Mo2C loaded N, P co-doped carbon nanospheres of claim 8 or the electrode of claim 9 are used in the electrolysis of water to produce hydrogen.